Breeding Objectives Indicate Value of Genomics for Beef Cattle - M. D. MacNeil (Kansas Agricultural Experiment Station Research Reports, 2016)
Genomics may have much to offer in the implementation of breeding objectives. Advantages of genomic prediction include increased accuracy of expected progeny differences (EPDs) for traits that have been components of routine genetic evaluations. Perhaps more importantly, genomic prediction makes it possible to include traits that are too costly or too difficult to measure, and traits that are measured too late in life or are sex-limited such that candidates for selection cannot have EBV with high accuracy at the time when selection decisions are made. Genomically enhanced EPDs may also allow for a marked reduction in generation interval, thus accelerating the annual rate of genetic improvement. Here, the value of genomic prediction, on a trait-by-trait basis, is extended to explore the contribution of genomic prediction to selection for a multitrait breeding objective indicative of economic merit. A simple two-trait objective indicative of feed efficiency is illustrated first, followed by objectives for terminal and maternal strains of Angus.
Keywords: multi-trait; selection; genomics